A novel drug susceptibility testing AIEgen with spatiotemporal resolved progress-reporting characteristic for therapy of drug-resistant tumor. (December 2022) - Zou, Hang; Gan, Shifeng; Shen, Hanchen; He, Benzhao; Zheng, Zheng; Li, Jingjun; Huang, Jacob C.; Zheng, Lei; Tang, Ben Zhong; Zhang, Jing
Graphical abstract: A novel, simple but powerful photosensitizer was developed. It can achieve fluorescent visual discrimination of different kinds of living cells and dead cells and developed into an ultrafast, precise and reliable drug susceptibility test platform to report the therapeutic effect of different clinical chemotherapeutic drugs. Moreover, it can exert ultraefficient photodynamic therapy towards drug-resistance tumor with self-reporting ability. Abstract: Drug resistance has become the biggest challenge in cancer treatments today. Addressing this problem seems to be an insurmountable challenge due to the underlying immensely complicated mechanisms. Thus, great endeavors have been devoted to solving this issue. Herein, a novel, simple but powerful photosensitizer, called ITPM, with aggregation-induced emission characteristic is developed and demonstrated to hold enormous potential to address drug resistance. This system can achieve fluorescent visual discrimination of living cells and dead cells due to its unique double-targeting ability, thus it can be developed into an ultrafast, precise and reliable drug susceptibility testing platform to report the therapeutic effect of different clinical chemotherapeutic drugs. Moreover, ITPM can exert efficient photodynamic therapy towards drug-resistant tumor, and simultaneously itself can enable real-time and in situ self-reporting to its treatment progress via spatiotemporal resolved fluorescent migration from cell membrane to nucleus . Therefore, such a superb system is expected to be a high-performance multifunctional theranostic platform for clinical application and provides great inspiration for tackling the issue of clinical drug resistance.